2002
DOI: 10.1002/1521-3757(20020503)114:9<1534::aid-ange1534>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Strukturübergänge in Clustern

Abstract: Lagert man an einen Cluster aus einzelnen Teilchen weitere Teilchen an, so bleibt die energetisch günstigste Grundstruktur weder erhalten noch ändert sie sich kontinuierlich. Stattdessen findet man Größenbereiche mit jeweils einem stark dominierenden Bauprinzip und vergleichsweise schmale Grenzen zwischen diesen Bereichen. Die Struktur des Festkörpers wird in der Regel erst nach mehreren Strukturübergängen bei relativ großen Clustern erreicht. Für das Auftreten dieser Strukturübergänge scheint es keine Rolle z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 281 publications
(212 reference statements)
0
5
0
Order By: Relevance
“…Before presenting further key results, we would like to point out that EA methods such as those used here do not provide just a single “best” structure but a large set of low‐energy structures. Via built‐in diversity enforcements, we ensure that this set does not contain only identical copies or minor variations of the best structure. Unless noted otherwise, the results presented here are typical for the lowest energy structures in this set, including the best one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before presenting further key results, we would like to point out that EA methods such as those used here do not provide just a single “best” structure but a large set of low‐energy structures. Via built‐in diversity enforcements, we ensure that this set does not contain only identical copies or minor variations of the best structure. Unless noted otherwise, the results presented here are typical for the lowest energy structures in this set, including the best one.…”
Section: Resultsmentioning
confidence: 99%
“…This entailed a demand for theoretical methods that can find optimal three‐dimensional arrangements of atoms or molecules in a huge search space increasing exponentially with particle number. This demand was met with a wide variety of nondeterministic global optimization methods, for example, simulated annealing, Monte‐Carlo (MC) with minimization (also known as basin‐hopping), and genetic/evolutionary algorithms (GA, EA) …”
Section: Introductionmentioning
confidence: 99%
“…To obtain reliable global minima for the stoichiometric clusters [(V 2 O 5 ) n A C H T U N G T R E N N U N G (SiO 2 ) m ] + , the geometry optimizations were performed starting from a high number of possible candidate structures (more than 200 for each cluster) generated from a systematic search based on the topological structures, and also a simplified basin-hopping method, [86] the details of which are described in the Supporting Information. Further computations using special methods, such as the strict basin-hopping method or genetic algorithm, [20,87,88] may be necessary to confirm that our search was sufficient to obtain the global minima. + + C 2 H 4 !…”
Section: Methodsmentioning
confidence: 98%
“…It has been shown that such coverage is necessary for a quantitatively correct description of solvation 41. Global cluster‐structure optimization32, 34 was used to generate optimal conformations of these 50 explicit water molecules, by employing the program package OGOLEM33 and multiple runs per case (five for the reactant complex, transition state, and product complex). To maintain a reasonable balance between accuracy and sufficient conformational exploration of the search space, these global structure optimizations were performed at the force‐field level, by using the OPLS‐AA force field for the reaction center and the TIP4P water model.…”
Section: Methods and Techniquesmentioning
confidence: 99%